Supervisi Akademik dalam Meningkatkan Kualitas Pembelajaran di Pendidikan Vokasi: Studi Kualitatif di SMK Negeri - Anugerah, Jonanda; Santosa, Eka Budhi (Universitas Sebelas Maret, 2025)
Supervision responsibility is one of the responsibilities that must be carried out by the principal as a teacher with additional duties at school. Therefore, this study aims to determine the implementation of these supervisory responsibilities to the principal of SMK Negeri 1 Pedan Klaten. This research was conducted in June 2024. The design used in this research is qualitative with interview techniques. Data were obtained from interviews with the head of SMK Negeri 1 Pedan Klaten and analyzed by qualitative descriptive method. Based on the analysis, it is known that the principal supervision program has been implemented in the school with procedures that are in accordance with the established supervision standards and the suggested supervision objectives are to improve the quality of learning in the school.